REVISITING IMAM AHMAD BIN HANBAL’S BACKGROUND AND THOUGHTS - Putri, Yulita; Nurhuda, Abid; Lira, Adelia Apriska; Aurora, Bunga; Lathif, Nur Muhammad (UIN Antasari Banjarmasin, 2024)
Abstract Islamic law provides many methods for deciding a case, starting from the lafdziyah method to the makawiyah method carried out by four madzhab imams, one of whom is famous is Imam Ahmad Bin Hanbal. This research aims to describe the history of the life and thoughts of Imam Ahmad Bin Hanbal. The method used is qualitative with literature study techniques then descriptive analysis is carried out. The research results show that Imam Ahmad Bin Hanbal is a Sunni Islamic cleric from Baghdad, Iraq. His thinking tends towards literalism and conservatism in the interpretation of religion. This is because the legal istinbath method used by him is based on Nash (Al-Quran and Sunnah), Fatwa of the Companions, Mursal hadith, dha'if hadith, and Qiyas. One example of the application of legal istinbath in fiqh carried out by Imam Ahmad Ibn Hanbal is regarding the law on female judges in Islam where he believes that women should not be judges based on Nash Al-Quran surah An-Nnisa verse 34. However, in the current era, it is less relevant if it continues to be implemented because the ability to become a leader, judge, or any other profession should not be based on gender. This is also in line with the thoughts of Yusuf Al-Qardawi and several contemporary scholars who have gender-friendly thoughts. Keywords: History of the Life; Thoughts; Imam; Ahmad bin Hanbal.